Community perception and acceptability of COVID-19 vaccine in South-West Nigeria: an online cross-sectional study - Adenike Iyanuoluwa Olugbenga-Bello; Olayinka Oluwabusola Bamidele; Oluwatosin Ruth Ilori; Roseline Olabisi Ige; Norbertta Ekpen Anegbe (AOSIS, 2023)
Background. The development of COVID-19 vaccines holds great potential for controlling the spread of SARS-CoV-2. Vaccines, irrespective of the disease are generally fraught with hesitancy, and Nigeria has a history of vaccine hesitancy. Objective. This study aimed at determining the perception of community members about the COVID-19 vaccine and their readiness to accept the vaccine in South West, Nigeria. Methods. A descriptive cross-sectional study design was employed to collect data from consenting adults using a structured online questionnaire for a period of three weeks. Data were subjected to a Chi-square test and logistic regression for bivariate and multivariate analysis, respectively. Results. A total of 807 respondents participated in the survey with 57.7% males and 42.3% females. Forty-five respondents (5.6%) had previously been diagnosed with COVID-19 while 11.5% of the respondents had co-morbidity. The overall perception of COVID-19 vaccines was good. Fifty-nine (59%) percent of the respondents were willing to accept the vaccine and will also encourage their family members to take the vaccine. Vaccine origin and cost were determinants of vaccine acceptability. Nonacceptability of the vaccine (61.6%) was based on possible adverse effects of the vaccine and mistrust of the government. Educational level, skill status, type of employment, and sector of employment were associated (P0.001) with the acceptability of the COVID-19 vaccine. Conclusions. Citizens were willing to take COVID-19 vaccines, however, a lack of trust in government programs might undermine the vaccine campaign. Hence, the government needs to rebuild trust with the citizens towards achieving a high vaccination rate for COVID-19.